Evaluation of a Radiolabeled Macrocyclic Peptide as Potential PET Imaging Probe for PD−L1. (28th April 2022) - Jouini, Nedra; Cardinale, Jens; Mindt, Thomas L.
Abstract: The interaction between the immune checkpoint PD‐1 and PD−L1 promotes T‐cell deactivation and cancer proliferation. Therefore, immune checkpoint inhibition therapy, which relies on prior assessment of the target, has been widely used for many cancers. As a non‐invasive molecular imaging tool, radiotracers bring novel information on the in vivo expression of biomarkers (e. g., PD−L1), enabling a personalized treatment of patients. Our work aimed at the development of a PD−L1‐specific, peptide‐based PET radiotracer. We synthesized and evaluated a radiolabeled macrocyclic peptide adapted from a patent by Bristol Myers Squibb. Synthesis of [ 68 Ga]Ga‐NJMP1 yielded a product with a radiochemical purity>95 % that was evaluated in vitro . However, experiments on CHO−K1 hPD−L1 cells showed very low cell binding and internalization rates of [ 68 Ga]Ga‐NJMP1 in comparison to a control radiopeptide (WL12). Non‐radioactive cellular assays using time‐resolved fluorescence energy transfer confirmed the low affinity of the reported parent peptide and the DOTA‐derivatives towards PD−L1. The results of our studies indicate that the macrocyclic peptide scaffold reported in the patent literature is not suitable for radiotracer development due to insufficient affinity towards PD−L1 and that C‐terminal modifications of the macrocyclic peptide interfere with important ligand/receptor interactions. Abstract : Immune checkpoint targeting : Inhibiting the interaction between the immune checkpoint PD‐1 and its ligand PD−L1 activates the immune system to fight cancer. Detection of the expression of PD−L1 is a prerequisite for immune checkpoint inhibition therapy. We report our investigations towards the development of a PD−L1 specific nuclear imaging probe based on a macrocyclic peptide scaffold reported in the patent literature.